NEUTROPHIL TO LYMPHOCYTE RATIO MEAN DIFFERENCE AMONG PEDIATRIC COVID-19 PATIENTS IN BALI: PRELIMINARY STUDY - Maharani, Ni Luh Putu Silfia; Masyeni, Sri; Trisnia, Putu Ayunda; Paramasatiari, Anak Agung Ayu Lila (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
The Neutrophil-to-Lymphocyte Ratio (NLR) is a significant prognostic marker in COVID-19, reflecting the body's inflammatory immune response. This study aimed to analyze differences in mean NLR among paediatric COVID-19 patients in Bali, stratified by age and gender. A cross-sectional analytic study was conducted using data from 56 hospitalized paediatric patients at Sanjiwani Gianyar and Wangaya Hospitals. The sample comprised patients aged 0–18 years, distributed as follows: 0–5 years (41.1%), 5–10 years (32.1%), 10–15 years (21.4%), and 15–18 years (5.4%). The cohort included 31 males (55.4%) and 25 females (44.6%). Statistical analysis using the Kruskal-Wallis test revealed a significant difference in mean NLR across age groups (p = 0.037). Similarly, the Mann-Whitney test indicated a significant difference in mean NLR between genders (p = 0.004). These findings suggest that the inflammatory response to COVID-19 varies among paediatric patients by both age and gender. Consequently, clinicians should consider these demographic factors, as they may indicate a need for tailored therapeutic and monitoring strategies.